Role of [18F]Fluorodeoxyglucose Positron Emission Tomography—Computed Tomography, Sonography, and Sonographically Guided Fine–Needle Aspiration Biopsy in the Diagnosis of Axillary Lymph Nodes in Patients With Breast Cancer: Comparison of Diagnostic Performance. (1st June 2014) - Sohn, Yu-Mee; Hong, Il Ki; Han, Kyunghwa
Abstract : Objectives: The aim of this study was to compare the diagnostic performance of [ 18 F]fluorodeoxyglucose (FDG) positron emission tomography–computed tomography (PET‐CT) with that of sonography and sonographically guided fine‐needle aspiration (FNA) for determining the preoperative axillary lymph node (ALN) status and to evaluate the factors related to false‐negative PET‐CT, sonographic, and FNA results in ALN staging of invasive ductal carcinoma. Methods: From March 2009 to July 2012, 226 patients had a diagnosis of primary breast cancer. Among these patients, 107 constituted the study population after exclusion of transferred patients and patients with breast cancer other than invasive ductal carcinoma. The diagnostic performance of the modalities was compared with pathologic reports. Univariate and multivariate analyses were used to evaluate the relationship between clinicopathologic factors (symptoms, T stage, hormone receptors, and histologic grade), false‐negative results, and true‐negative results on PET‐CT, sonography, and FNA. Results: Of the 107 patients, 45 (42.1%) had positive results on final pathologic analysis of ALNs. Sonographically guided FNA had a significantly higher specificity, positive predictive value, accuracy, and area under the receiver operating characteristic curve than sonography and PET‐CT ( P < .01). When sonography and PET‐CT were combined, the sensitivity was significantly improved ( P = .019) compared with sonography alone. When FNA and PET‐CT were combined, the sensitivity and negative predictive value were significantly increased compared with each modality ( P < .01). Conclusions: Sonographically guided FNA was found to be an excellent diagnostic tool for preoperative evaluation of the ALN status. To obviate the step of sentinel lymph node biopsy for determining the ALN status, combined evaluation of ALNs by these modalities may be more complementary than the use of a single modality.